Bulletin of the AAS 2021
DOI: 10.3847/25c2cfeb.4c2df948
|View full text |Cite
|
Sign up to set email alerts
|

New Frontiers Titan Orbiter

Abstract: As one of two planetary objects (other than Earth) that have solid surfaces, thick atmospheres, and astrobiological significance, Titan, like Mars, merits ongoing study with multiple spacecraft. We propose that a Titan orbiter dedicated to geophysics, geology, and atmospheric science be added to the New Frontiers menu for the coming decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Even though aerocapture is not currently considered for the Uranus Orbiter and Probe which is the top priority for the Flagship mission of the next decade [22,23], studies have shown aerocapture offers significant mission design advantages [24]. Aerocapture has also been shown to provide signficant benefits for a New Frontiers class Titan orbiter [25,26], and a Neptune Flagship mission [27,28].…”
Section: Applications For Future Missionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though aerocapture is not currently considered for the Uranus Orbiter and Probe which is the top priority for the Flagship mission of the next decade [22,23], studies have shown aerocapture offers significant mission design advantages [24]. Aerocapture has also been shown to provide signficant benefits for a New Frontiers class Titan orbiter [25,26], and a Neptune Flagship mission [27,28].…”
Section: Applications For Future Missionsmentioning
confidence: 99%
“…The Dragonfly mission will deliver a relocatable lander to Titan's surface. An orbiter around Titan remains to be accomplished by a future mission [25,26]. However, getting into orbit around Titan requires very large ΔV, which requires enormous propellant and hence drives up the wet mass and mission cost.…”
Section: Titanmentioning
confidence: 99%